2019
DOI: 10.3390/s19112620
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Recognition of the Emotions of People with Visual Disabilities through Brain–Computer Interfaces

Abstract: A brain–computer interface is an alternative for communication between people and computers, through the acquisition and analysis of brain signals. Research related to this field has focused on serving people with different types of motor, visual or auditory disabilities. On the other hand, affective computing studies and extracts information about the emotional state of a person in certain situations, an important aspect for the interaction between people and the computer. In particular, this manuscript consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Start the EEG Data Acquisition in Automatic Mode. 4. According to both visual and auditory indicator, from 2 to 2 seconds, the user should execute one eye-blink.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Start the EEG Data Acquisition in Automatic Mode. 4. According to both visual and auditory indicator, from 2 to 2 seconds, the user should execute one eye-blink.…”
Section: Resultsmentioning
confidence: 99%
“…Brain-Computer Interface is a multidisciplinary research field, which comprises achievements in related scientific and technical areas: artificial intelligence, computer science, mechatronics [1][2][3], signal processing, neuroscience and psychology [4]. The aim of a brain-computer interface system is related to helping people with neuromotor disabilities, who cannot communicate with the outside environment by using natural paths, such as muscles and peripheral nerves.…”
Section: Introductionmentioning
confidence: 99%
“…Brain-Computer Interface is a multidisciplinary research field, which comprises achievements in related scientific and technical areas: artificial intelligence, computer science, mechatronics [1][2][3], signal processing, neuroscience, and psychology [4]. Beyond its various applications in non-clinical fields (digital games, sleep avoidance, mental states monitoring, advertisement, and business), the fundamental aim of a brain-computer interface system is related to helping people with neuromotor disabilities who cannot communicate with the outside environment by using natural paths, such as muscles and peripheral nerves.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, this paper's authors analyzed the research that proposes the classification of emotions in people with visual disabilities (López-Hernández et al, 2019). The results showed that new approaches that specifically consider people with visual disabilities and the study of their emotions are still required.…”
Section: Introductionmentioning
confidence: 99%